Pyrazine analogs are active components of wolf urine that induce avoidance and fear-related behaviors in deer - Osada, Kazumi; Miyazono, Sadaharu; Kashiwayanagi, Makoto (Frontiers in Behavioral Neuroscience, 2014)
Our previous studies indicated that a cocktail of pyrazine analogs, identified in wolf urine, induced avoidance and fear behaviors in mice. The effects of the pyrazine cocktail on Hokkaido deer (Cervus nippon yesoensis) were investigated in field bioassays at a deer park in Hokkaido, Japan. A set of feeding bioassay trials tested the effects of the pyrazine cocktail odor on the behavior of the deer located around a feeding area in August and September 2013. This odor effectively suppressed the approach of the deer to the feeding area. In addition, the pyrazine cocktail odor provoked fear-related behaviors, such as “tail-flag”, “flight” and “jump” actions, of the deer around the feeding area. This study is the first experimental demonstration that the pyrazine analogs in wolf urine have robust and continual fearful aversive effects on ungulates as well as mice. The pyrazine cocktail might be suitable for a chemical repellent that could limit damage to forests and agricultural crops by wild ungulates.